Hyperhomocysteinemia and Juvenile Open Angle Glaucoma - A Rare Association - Sonal Dangda; Usha Yadava (Delhi Journal of Ophthalmology)
A young female diagnosed as juvenile open angle glaucoma was noted to have disc collaterals, retinal venous tortuosity and lens subluxation. Serum homocysteine levels were raised while vitamin B12 was found to be low. A genetic work up showed polymorphism of MTHFR 1298C gene. Heterozygous mutations like these when influenced by various lifestyle or nutritional factors i.e., nutrigenomic presentation, may show subtle manifestations and severe form of systemic disease is rarely present.